2013
DOI: 10.1021/cm402897c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Separations in Metal–Organic Frameworks

Abstract: New materials capable of separating mixtures of saturated, unsaturated, and aromatic hydrocarbons can enable more efficient industrial processes and cleaner energy. Outstanding challenges in hydrocarbon separations stem from the similar structures, properties, and reactivities of the molecules comprising many of these mixtures. With high surface areas, tunable pore geometries, and adjustable surface functionality, metal−organic frameworks hold tremendous promise for effecting previously difficult or impossible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
399
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(408 citation statements)
references
References 207 publications
5
399
1
3
Order By: Relevance
“…It was recently shown that in alkane/alkene separations open metal sites (OMS) of MOFs can bind the alkene more strongly than the alkane due to the formation of π-complexation bonds between alkene and OMS of MOFs. (Herm et al, 2014) For example, CuBTC, which has a high density of OMS, was experimentally studied and adsorption of C 2 H 4 on CuBTC was reported to be higher than that of C 2 H 6 . (Martins et al, 2015) A recent study showed that conventional "off-the-shelf" molecular models, based on the LJ potential, become unable to describe the specific and localized nature of the interactions between C 2 H 4 and OMS of MOFs and detailed quantum-level calculations must be used to accurately define these interactions Dreiding (Mayo et al, 1990) force field was used for all framework atoms.…”
Section: Molecular Simulationsmentioning
confidence: 99%
“…It was recently shown that in alkane/alkene separations open metal sites (OMS) of MOFs can bind the alkene more strongly than the alkane due to the formation of π-complexation bonds between alkene and OMS of MOFs. (Herm et al, 2014) For example, CuBTC, which has a high density of OMS, was experimentally studied and adsorption of C 2 H 4 on CuBTC was reported to be higher than that of C 2 H 6 . (Martins et al, 2015) A recent study showed that conventional "off-the-shelf" molecular models, based on the LJ potential, become unable to describe the specific and localized nature of the interactions between C 2 H 4 and OMS of MOFs and detailed quantum-level calculations must be used to accurately define these interactions Dreiding (Mayo et al, 1990) force field was used for all framework atoms.…”
Section: Molecular Simulationsmentioning
confidence: 99%
“…10 Because of their ultrahigh porosity and the possibility of functionality, they play an important role in gas adsorption and separation. [11][12][13][14][15] For instance, MOFs are becoming one of the most promising candidates to reduce carbon dioxide (CO 2 ) emissions, which is useful to resolve the increasingly severe global warming problem. 13,16,17 However, very limited MOFs show satisfactory CO 2 capture performance at low pressure and ambient temperature due to the weak interaction between CO 2 and the frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their modular nature and permanent porosity, they have been used for various applications, including gas storage [5][6][7][8][9], separation [10][11][12][13], magnetism [14][15][16], transport [17][18][19][20][21], and catalysis [22][23][24][25][26][27]. Gas storage is one of the most promising applications of MOFs due to their porosity and tunability.…”
Section: Introductionmentioning
confidence: 99%